Autophagy in Tissue Injury and Homeostasis - Lin, Pei-Hui (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Autophagy ("auto-digestion"), a lysosome-dependent process, degrades and turns over damaged or senescent organelles and proteins. Autophagy is a highly regulated process that impacts several vital cellular responses, including inflammation, cell death, energy metabolism, and homeostasis of organelles (mitochondria and others). Although the role of autophagy in the maintenance of tissue homeostasis is well documented, its role during tissue injury and regeneration is still emerging. In this Special Issue on "Autophagy in Tissue Injury and Homeostasis", we focus on the roles of autophagy in systemic, specific tissue (organs/cells) injury or organ failure associated with sepsis, inflammation, metabolic disorder, toxic chemicals, ischemia-reperfusion injury, hypoxic oxidative stress, tissue fibrosis, trauma, and nutrient starvation. The knowledge gained from the identification and characterization of new molecular mechanisms will shed light on biomedical applications for tissue protection through the modulation of autophagy.